Accountability of local and state governments in India: an overview of recent research. Issue 1 (2014) - ,
Abstract : Purpose – This paper aims to provide an overview of recent research on accountability of local and state governments in India.Design/methodology/approach – The Downsian theory of electoral competition is used as a departure point for classifying different sources of government accountability failures. Subsequent sections deal with each of these sources in turn: limited voter participation and awareness; ideology, honesty and competence of political parties and electoral candidates; capture by elites; clientelism and vote‐buying. Each section starts by explaining the relevant departure from the Downsian framework and then reviews available empirical evidence in the Indian context for each of these possible "distortions", besides effects of related policy interventions. The final section summarizes the lessons learnt, and the fresh questions that they raise.Findings – The paper describes a range of possible reasons that limit the effectiveness of elections as a mechanism inducing governments to be accountable to their citizens and reviews the evidence available from the Indian context concerning each of these.Originality/value – The contribution of the paper is to provide an overview and perspective of recent literature on political economy problems affecting performance of state and local governments in India. Acknowledgements : Text of the P.G. Kumar Memorial Lecture delivered at the Centre for Development Studies (CDS), Trivandrum on July 26, 2012. The author is very grateful to CDS for their invitation and hospitality, and to the audience for their questions and feedback. The author is also grateful to Maitreesh Ghatak, Vijayendra Rao and Sandip Sukhtankar for useful suggestions.